Site-specific formation of metastable OCS2+ studied by Auger-electron-ion coincidence method. (19th May 2015) - Kaneyasu, T; Ito, M; Soejima, K; Hikosaka, Y; Shigemasa, E
Abstract: We have studied the site-specific formation of metastable OCS 2+ in the C1s and the O1s Auger decays of OCS molecules by using an Auger-electron–ion coincidence technique. The coincidence measurement reveals the metastable character of the Auger final states with the (3 π ) −2 configuration. The formation of metastable OCS 2+ is observed negligibly in the C1s Auger decay and only weakly in the O1s Auger decay, in contrast to the favorable metastable formation previously reported for S2p Auger decay. It is found that the origin of the site-specificity in the formation of metastable OCS 2+ arises from the localization effect of the valence orbital involved in the Auger transition. The dissociative dication states related to individual fragmentation pathways are also derived from the coincidence measurement.